Reconciling ecosystem service supply-demand mismatches through ecological compensation in the Tibetan plateau - Wenjie Yao; Xiaofeng Wang; Zixu Jia; Xiaoxue Wang; Xinrong Zhang; Xiaoming Feng; Jitao Zhou; Jiahao Ma; You Tu; Xueren Liu; Zechong Sun (Carbon Balance and Management)
Abstract Accurately identifying ecological compensation (EC) regions and establishing clear compensation criteria are essential for promoting carbon sequestration, mitigating ecological degradation, and supporting equitable resource allocation. In this study, ecological modeling combined with hotspot analysis was applied to quantify the spatial mismatch between ecosystem service (ES) supply and demand on the Tibetan Plateau (TP) in 2020. We introduced the concept of comparative ecological radiation force (CERF) to characterize the spatial flow of ESs and to estimate the total compensation required to balance these flows. Our results highlight that the value of carbon sequestration, represented by net primary production (NPP), reached 1.21 × 10⁶ CNY, alongside other key services such as soil conservation (SC) (284.69 × 106 CNY), water yield (WY) (44.99 × 106 CNY) and food supply (FS) (20.81 × 106 CNY). The directional analysis of service flows revealed that NPP, along with SC and WY, predominantly flowed from east to west, while FS exhibited a north-to-south pattern. Notably, NPP received only 0.16% of the total ecological compensation, in contrast to 95.42% for SC, 4.21% for WY, and 0.21% for FS. This study provides an integrated framework for aligning EC strategies with carbon management goals, offering insights to support carbon neutrality efforts and ecosystem restoration on the TP.